Muscular Diagnostics and the Feasibility of Microsystem Acupuncture as a Potential Adjunct in the Treatment of Painful Temporomandibular Disorders: Results of a Retrospective Cohort Study. Issue 6 (December 2018) - Simma, Irmgard; Simma, Leopold; Fleckenstein, Johannes
Aims: To investigate the effect of microsystem acupuncture on painful temporomandibular disorders (TMD). Methods: We retrospectively analysed 887 treatments in 407 TMD-patients (mean age 45±1.5 years), who received microsystem acupuncture (mouth, scalp or fingers) with a focus on oral acupuncture. All patients systematically underwent palpation of specific muscular tender points and their pain rating was assessed on a four-point Likert scale (no pain to strong pain) before and after treatment. In 42 cases, the pain intensity was determined using a visual analogue scale (0–100 mm). As the data were normally distributed, analysis was performed with unpaired t-tests. Results: The pterygoid muscles were most painful to palpation, with the lateral pterygoid rated moderate to strong by 76% of patients and the medial pterygoid by 48% of patients. The palpation of microsystem acupuncture points revealed the strongest sensitivity (moderate or strong pain) of the oral retromolar points at the upper jaw (83%). After treatment, the pain intensity of all tender points had significantly decreased (P<0.001). The proportion of moderate to strong pain ratings was below 3% at most tender points. Overall pain intensity of the subjects (n=42) before treatment was 55.5±19.7 mm on the VAS scale and was significantly reduced to 29.6±20.9 mm (P<0.001) post-treatment. Conclusions: This analysis suggests microsystem acupuncture could reduce the pain intensity of TMD in the short term. Considering the increased local muscular tenderness, further investigations regarding the key role of myofascial trigger points in the occurrence of TMDs are warranted and could lead to new comprehensive treatment strategies.